Usage of Smartphones by Prospective Teacher-Educators in Central University of Jammu - Vanguri , Ravi (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The Information and Communication Technology (ICT) tools are very powerful and playing a vital role in higher education, particularly to gain information, to have deep understanding about the concepts, and useful for self-improvement in academics. The smartphone is one of the powerful platforms to learn at any time, at any place and easy to carry anywhere. Different applications installed in Smartphones have provided facility to access various e-learning material in the form of audio, videos, and read material, etc. The present study aimed to ascertain the use of Smartphone with respect to learning academic courses, extent of its usage and impact on learning while pursuing their Master of Education Programme. The present study adopted descriptive survey method and purposive sampling technique. A total of fifty-two prospective teacher-educators of Master of Education (M.Ed.) programme of Central University of Jammu constituted as sample and a self-constructed semi-structured questionnaire was administered The target-group. The study findings revealed that all the prospective Teacher-Educators were using smartphones to improve their understanding of academic courses. Majority of the prospective teacher-educators were found to have lack of awareness about smartphone precautions and also seeking training/orientation to use it effectively. 92% of prospective teacher-educators responded that using smartphone in the class will engender distractions to lecturers/mentors and firmly dissented to using smartphones during lecturing in the class. Majority of the prospective teacher-educators opined that using smartphone categorically wasting their valuable time (61.53%), smartphones have some drawbacks (92.30%) and also believed to be addicted to use of smartphones (76.92%) in their day-to-day life.